(untitled) (Economic and Political Thought, 2019)
The Central Industrial District [Centralny Okręg Przemysłowy (COP)] has been the object of scientific deliberations, analyses and research works for years. The study presents its origin and various stages of the project implementation. The silhouette of the main founder of COP, Eugeniusz Kwiatkowski, the Minister of the Treasury and the Deputy Prime Minister is presented, outlining his main idea, which led him to create a strategy for Poland. Mentioning the most important investments carried out in COP, the author shows their considerable momentum and scope. The ability to engage human capital on such a large scale shows the character of that generation, their great desire to build a safe and prosperous country for the good of future generations. The establishment of the Central Industrial Region was Poland and Poles’ success, raising their quality of life and providing a guarantee of sustainable development of the national economy. The COP infrastructure and some industrial plants built there have been used by present generations until now. The study compares COP to the Strategy for Responsible Development, defining common features and indicating the directions of Poland’s economic development in both historical periods.